2018
DOI: 10.1016/j.jbi.2018.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Identification of target gene and prognostic evaluation for lung adenocarcinoma using gene expression meta-analysis, network analysis and neural network algorithms

Abstract: Our study has identified novel candidate biomarkers, pathways, transcription factors (TFs), and kinases associated with NSCLC prognosis, as well as drug candidates, which may assist treatment strategy for NSCLC patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(32 citation statements)
references
References 73 publications
1
30
0
Order By: Relevance
“…Thus, we performed integrated biological network analysis to identify the potential target genes (PTGs) of the shared cmiRNA signatures BSO and ASO of LUAD samples. Microarray analysis of gene expression profiles is a standard and well-known method to identify key hub genes and pathways [19,20]. Initially, we collected the cmiRNA and cmRNA datasets from the Gene Expression Omnibus (GEO) database.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, we performed integrated biological network analysis to identify the potential target genes (PTGs) of the shared cmiRNA signatures BSO and ASO of LUAD samples. Microarray analysis of gene expression profiles is a standard and well-known method to identify key hub genes and pathways [19,20]. Initially, we collected the cmiRNA and cmRNA datasets from the Gene Expression Omnibus (GEO) database.…”
Section: Introductionmentioning
confidence: 99%
“…However, different expression profile with various research background provided diverse results. [ 5 8 ] For example, Gurudeeban et al presented that EGR-1 was associated with NSCLC through network analysis. [ 5 ] Bai, et al showed that KIF2C in association with progression in lung adenocarcinoma.…”
Section: Introductionmentioning
confidence: 99%
“…[ 5 8 ] For example, Gurudeeban et al presented that EGR-1 was associated with NSCLC through network analysis. [ 5 ] Bai, et al showed that KIF2C in association with progression in lung adenocarcinoma. [ 6 ] Ying, et al pointed that AURKB might a hub gene in NSCLC.…”
Section: Introductionmentioning
confidence: 99%
“…Bioinformatics analysis surfaces with the emergence of massive gene data, and is a powerful methodology that can be used in discovering disease-causing genes, biomarkers, and therapeutic targets through global analysis. For example, using bioinformatics analysis methods, Gurudeeban Selvaraj, et al [16] identifi ed that mitogen-activated protein kinase 1 and aurora kinase are the hub nodes and identifi ed candidate drugs in lung adenocarcinoma. However, the application of bioinformatics analysis methods in kidney diseases has just started.…”
Section: Introductionmentioning
confidence: 99%